The Moderating Role of Profit and Loss Sharing in the Relationship Between Marketability and Profitability in Islamic Commercial Banks in Indonesia - Catur Surya Perwira; Sugeng Wahyudi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The problem phenomenon in this study is the low growth of marketability, profitability, profit and loss sharing of Islamic banks in 2014-2019. This study aims to analyze the factors that influence the profitability of Islamic commercial banks in Indonesia for the period 2014-2019. This research method uses quantitative with secondary data sources. The results of the study of factors that have a significant positive effect are Profit and loss sharing on profitability with a t-count value of 6.13091 > t-table 1.645. Marketability to profitability with t-count of 2.00583 > t-table 1.645 and which has a significant negative effect. Marketability on profit and loss sharing t-count 6.80506 > t-table 1.645 and original sample coefficient 1 -0.35806.